DAMPAK CORAL BLEACHING PADA MASYARAKAT LOKAL DI KAWASAN TAMAN LAUT BUNAKEN - A. Muhammad Fauzan Sulfa; Nabilah Rezky Putri Zahirah; Fuad Mahfud Assidiq (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2024)
Coral bleaching is a phenomenon in which corals or coral reefs lose their colour due to environmental stress. An example of coral bleaching that occurred in Indonesia is in the Bunaken marine park area, located on the island of Manado, North Sulawesi. The Bunaken marine park area is famous for underwater tourism and the many types of coral reefs that can be found. Based on data, coral bleaching cases have increased from year to year. This threatens the tourism industry, weakens the natural protection of the coast and harms the livelihoods of fishermen who depend on coral reefs, so special attention is needed to deal with the problems that are happening. The writing of this article was prepared using the literature study method. The purpose of writing this article is to find out the causes of coral bleaching and how the impact can be felt by local communities in the Bunaken National Park area, as well as explaining how efforts can be made to tackle coral bleaching that occurs. The impact of coral bleaching is very large on local communities in the Bunaken Marine Park area.